120. Stewardship Driven Reduction of Inappropriate Clostridioides difficile Testing at a Tertiary Military Medical Facility - Gilbert, Laura (Open Forum Infect Dis, 2020)
BACKGROUND: C. difficile infection (CDI) is the leading hospital associated (HA) infection in an era of antibiotic overuse and highly-sensitive PCR-based diagnostics. PCR does not differentiate CDI versus colonization making over-reporting a concern. HA-CDI can impact hospital reimbursement, lead to unnecessary treatment, increase costs and length of stay. Our aim was to implement an intervention to target inappropriate C. difficile (CD) testing. METHODS: Two-tiered testing is not utilized at our facility. After provider education on guidelines for appropriate CD testing, prompts were introduced into the electronic medical record (EMR) for CD test orders. At order input, providers are prompted to answer “yes” or “no” to two questions; 1) receipt of stool softeners within the preceding 48 hours and 2) criteria of 3 loose stools within 24 hours. The test order was completed regardless of the responses to the prompted questions. Six-month post-intervention data was compared to the same timeframe during the year prior. RESULTS: A total of 334 and 236 tests were ordered in the pre- and post-intervention periods respectively. Accounting for inpatient bed days, the incidence reduction rate (IRR) was 0.75 (CI 0.63–0.89, p < 0.001) corresponding to an estimated hospital cost-savings of $12,250 based on testing costs alone. The majority of CD tests were ordered by IM providers, who also demonstrated the greatest reduction in tests ordered post-intervention. Patient characteristics were analyzed in the pre- and post-intervention periods finding significantly less positive CD tests ordered for patients with recurrent C. difficileduring the post-intervention period (2 vs 7, p = 0.04). Patients who were transferred from another institution had significantly more positive CD tests in the post-intervention period (19 vs 7, p = 0.02). CONCLUSION: In conclusion, the results demonstrate that implementing a systems-based EMR initiative led to a 25% reduction in CD testing with a cost-savings of $12,250 not accounting for potential associated cost savings. This project suggests that even without restricting order access, educational prompts integrated in the EMR can have meaningful impact on stewardship endeavors to help reduce inappropriate CD testing. Sustained effect would be an area to explore. DISCLOSURES: All Authors: No reported disclosures